Chain stability in trading networks - John William Hatfield; Scott Duke Kominers; Alexandru Nichifor; Michael Ostrovsky; Alexander Westkamp (Theoretical Economics, 2021)
In a general model of trading networks with bilateral contracts, we propose a suitably adapted chain stability concept that plays the same role as pairwise stability in two-sided settings. We show that chain stability is equivalent to stability if all agents' preferences are jointly fully substitutable and satisfy the Laws of Aggregate Supply and Demand. In the special case of trading networks with transferable utility, an outcome is consistent with competitive equilibrium if and only if it is chain stable.
Keywords: C78; D85; L14; 330; Matching; trading networks; chain stability; stability; competitive equilibria; full substitutability; Laws of Aggregate Supply and Demand